(untitled) (Rome, 1990)
The present volume includes 8sea turtle species belonging to 2 families and 6 genera. It comprises an introductory section with general remarks on the systematics, habitat and fisheries of the family, a glossary of technical terms used, illustrated keys to genera and species, and detailed accounts on all species. Species accounts include drawing, scientific and vernacular names, information on habitat, biology and fisheries, and a distribution map.
Keywords: Sea turtles,Sinh vật học